Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.3 - Integrated Review - Summary on Solving Quadratic Equations: 17

Answer

$x_{1}= 2 + 3\sqrt{3}$ and $x_{2} = 2 - 3\sqrt{3}$

Work Step by Step

Given $(x-2)^2=27 \longrightarrow x^2-4x+4=27 \longrightarrow x^2-4x-23=0$ $a= 1, \ b=-4, \ c=-23$ Using the quadratic formula: $\dfrac{-b \pm \sqrt{b^2-4ac}}{2a}$ we have: $\dfrac{-(-4) \pm \sqrt{(-4)^2-4 \times 1\times (-23)}}{2 \times 1} = \dfrac{4 \pm \sqrt{16+92}}{2} = \dfrac{4 \pm \sqrt{108}}{2} = \dfrac{4 \pm 6\sqrt{3}}{2} = \\ 2 \pm 3\sqrt{3}$ Therefore the solutions are $x_{1}= 2 + 3\sqrt{3}$ and $x_{2} = 2 - 3\sqrt{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.